2020
DOI: 10.1101/2020.04.10.20060954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global convergence of COVID-19 basic reproduction number and estimation from early-time SIR dynamics

Abstract: The SIR ('susceptible-infectious-recovered') formulation is used to uncover the generic spread mechanisms observed by COVID-19 dynamics globally, especially in the early phases of infectious spread. During this early period, potential controls were not effectively put in place or enforced in many countries. Hence, the early phases of COVID-19 spread in countries where controls were weak offer a unique perspective on the ensemble-behavior of COVID-19 basic reproduction number R o . The work here shows that ther… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…We see that the basic reproduction number started in mid-March slightly above 4, around the values that several clinical studies have suggested. For example, see Table 1 in Katul et al (2020) for a list of estimates (the authors conclude that their best estimate of an unmitigated R 0,t for COVID-19 is 4.5, quite close to our result). However, R 0,t fell very rapidly and, by mid-April, it was well below 1.…”
Section: The Estimated Time-varying Reproduction Numberssupporting
confidence: 87%
“…We see that the basic reproduction number started in mid-March slightly above 4, around the values that several clinical studies have suggested. For example, see Table 1 in Katul et al (2020) for a list of estimates (the authors conclude that their best estimate of an unmitigated R 0,t for COVID-19 is 4.5, quite close to our result). However, R 0,t fell very rapidly and, by mid-April, it was well below 1.…”
Section: The Estimated Time-varying Reproduction Numberssupporting
confidence: 87%
“…(2020) European Union Linka et al. (2020) 4.5 Global (across many nations) Katul et al. (2020) 2.56 India Rai et al.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing herd immunity to control the COVID-19 epidemic is problematic. Given that the case fatality rate (CFR) of COVID-19 can range between 0.25% and 3.0% of a country’s population, the estimated number of people who could potentially die from COVID-19 for the population to reach a minimum (‘critical’) level of population immunity (P crit herd immunity level) may be difficult to accept [ 86 ]. Currently, the best way to minimize the loss of lives and the occurrence of severe cases requiring intensive care is to shelter vulnerable groups of individuals and slow the spread of the virus [ 87 ].…”
Section: Herd Immunity Effectivenessmentioning
confidence: 99%